prospective of the family in the socialization of community values (Revista Electrónica REDINE, 2018)
The family is considered as one of the fundamental bases of society, due to its socio-natural union, necessary for the teaching of values ​​that is based on the common good and the recognition of the collective principles that constitute the social fabric of each area of coexistence of a country. The purpose of this paper is to deliberate on the prospective of the family in the socialization of community values. The methodological process used relied on the documentary review of some theoretical approaches, which allowed reflective analysis to argue about aspects related to the conceptions of the family that place it as the nucleus of society; likewise, it fulfills an educational role, due to the power it has to lead the key elements in the formation of children through socializing patterns that constitute the beliefs, attitudes, norms, principles, among others, that shape their personality. Thus, the systems of civic, moral and ethical values ​​have individual and also community components, from a perspective that envisions the group of people who live together, under accepted, respected and practiced accepted social behaviors. The studied aspects allowed us to conclude that 21st century society requires that familiar constructs that are object of reflection, due to the influence that it has in the socializing process of values, from where the principles that result in generational modeling are transmitted from which transmit the bases of citizen behavior to live in the vision of personal and community well-being.
Keywords: prospective; family; socializing process; community values